The year of the locust : a thriller [large type] - Hayes, Terry, 1951- (Thorndike Press, a part of Gale, a Cengage Company, 2024)
If, like Kane, you're a Denied Access Area spy for the CIA, then boundaries have no meaning. Your function is to go in, do whatever is required, and get out again--by whatever means necessary. You know when to run, when to hide--and when to shoot. But some places don't play by the rules. Some places are too dangerous, even for a man of Kane's experience. The badlands where the borders of Pakistan, Iran, and Afghanistan meet are such a place--a place where violence is the only way to survive. Kane travels there to exfiltrate a man with vital information for the safety of the West--but instead he meets an adversary who will take the world to the brink of extinction. A frightening, clever, vicious man with blood on his hands and vengeance in his heart.--